2020
DOI: 10.1016/j.ijscr.2020.09.118
|View full text |Cite
|
Sign up to set email alerts
|

The treatment for refractory rectovaginal fistula after low anterior resection with estriol, polyglycolic acid sheets and primary closure: A case report

Abstract: Highlights Rectovaginal fistula is a refractory complication following low anterior resection for rectal cancer. Rectovaginal fistula is often managed with stoma creation, closure of the fistula and/or re-anastomosis. Our case was successfully treated with primary closure of the fistula following administration of estriol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, these healed cases were reported only as case reports [42,43]. The documented case reports in using vaginal or oral estriol tablet in addition to conservative therapy resulted in the closure of RVFs [44][45][46]. Summarizing the successful case reports after LAR, vaginal estriol tablet was given in eight patients without surgical intervention, and six of eight RVFs healed within 35 days.…”
Section: Rvfs After Low-anterior Resection (Lar)mentioning
confidence: 99%
“…However, these healed cases were reported only as case reports [42,43]. The documented case reports in using vaginal or oral estriol tablet in addition to conservative therapy resulted in the closure of RVFs [44][45][46]. Summarizing the successful case reports after LAR, vaginal estriol tablet was given in eight patients without surgical intervention, and six of eight RVFs healed within 35 days.…”
Section: Rvfs After Low-anterior Resection (Lar)mentioning
confidence: 99%
“…Notably, the diameter of the RVF with spontaneous healing reported in the literature was not larger than 1 cm. Some investigators have suggested giving concentrated coagulation factor XIII intravenously for 5 d during nonoperative treatment to promote fistula healing because this coagulation factor is decreased significantly in the early postoperative period and may interfere with wound healing[ 14 , 17 ]. A large survey of active members of the American Society of Colon and Rectal Surgeons in the 1990s identified a total of 57 RVF after low anterior resection, and 14 of them were managed conservatively.…”
Section: Managementmentioning
confidence: 99%
“…However, some of the patients receiving the endoscopic placement of self-expandable metal stents experienced stent dislodgement or severe tenesmus requiring stent removal. Other endoluminal interventions for treating RVF after low anterior resection reported in the literature include fibrin glue application[ 22 ], fistula coverage with polyglycolic acid sheet[ 17 ], endoluminal clipping[ 23 , 24 ], and transanal endoscopic suturing[ 25 ].…”
Section: Managementmentioning
confidence: 99%